Emerging Trend in the Pharmacotherapy of Osteoarthritis - Zhang, Wei; Robertson, William Brett; Zhao, Jinmin; Chen, Weiwei; Xu, Jiake (Frontiers in Endocrinology, 2019)
Osteoarthritis (OA) is a degenerative joint disorder and one of the most prevalent diseases among the elderly population. Due to the limited spontaneous healing capacity of articular cartilage, it still remains challenging to find satisfactory treatment for OA. This review covers the emerging trends of pharmacologic therapies for OA such as traditional OA drugs (acetaminophen, non-steroidal anti-inflammatory drugs (NSAIDs), opioids, serotonin-norepinephrine reuptake inhibitors (SNRIs), intra-articular injections of corticosteroids, and dietary supplements), which are effective in pain relief but not in reversing damage, and are frequently associated with adverse events. Alternatively, disease-modifying drugs provide promising alternatives for the management of OA. The development of these emerging OA therapeutic agents requires a comprehensive understanding of the pathophysiology of OA progression. The process of cartilage anabolism/catabolism, subchondral bone remodeling and synovial inflammation are identified as potential targets. These emerging OA drugs such as bone morphogenetic protein-7 (BMP-7), fibroblast growth factor-18 (FGF-18), human serum albumin (HSA), interleukin-1 (IL-1) inhibitor, β-Nerve growth factor (β-NGF) antibody, matrix extracellular phosphoglycoprotein (MEPE) and inverse agonist of retinoic acid-related orphan receptor alpha (RORα) etc. have shown potential to modify progression of OA with minimal adverse effects. However, large-scale randomized controlled trials (RCTs) are needed to investigate the safety and efficacy before translation from bench to bedside.